2019
DOI: 10.1080/2162402x.2019.1652538
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CTLA-4 blockade and interferon-α on clonality of T-cell repertoire in the tumor microenvironment and peripheral blood of metastatic melanoma patients

Abstract: Patients with metastatic melanoma were treated with tremelimumab and interferon-α (IFN) in a previously reported clinical trial [NCT00610857]. Responses were assessed by RECIST criteria as complete (CR) or partial (PR), stable disease (SD) or progressive disease (PD). In this study, T-cell receptor (TCR) beta-chain repertoire was immunosequenced in peripheral blood mononuclear cells (PBMC) specimens (N = 33) and tumor samples (N = 18) utilizing the immunoSEQ® Assay to determine repertoire clonality and T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In particular, the anti-CTLA4 resulted in increased diversity indices (richness and Shannon diversity index) upon treatment, and the higher diversity indices correlated with clinically observed toxicities but not with clinical response [71]. A similar lack of association between baseline peripheral TCR repertoire diversity and response was recently observed in patients treated with combination therapy of anti-CTLA4 and interferon-α [83].…”
Section: Metastatic Melanomasupporting
confidence: 56%
See 1 more Smart Citation
“…In particular, the anti-CTLA4 resulted in increased diversity indices (richness and Shannon diversity index) upon treatment, and the higher diversity indices correlated with clinically observed toxicities but not with clinical response [71]. A similar lack of association between baseline peripheral TCR repertoire diversity and response was recently observed in patients treated with combination therapy of anti-CTLA4 and interferon-α [83].…”
Section: Metastatic Melanomasupporting
confidence: 56%
“…An opposite findings was obtained by Postow et al, who reported that patients who had clinical benefit had a higher degree of richness and evenness in their peripheral baseline TCR repertoires than patients who did not have clinical benefit [77]. Although these studies utilized different CTLA-4 blocking antibodies (tremelimumab in [71,83] and ipilimumab in [77]) a more plausible explanation for the discrepant results would be due to the different methodologies they used, thus underlining even more the need to optimize and validate the methodology for the analysis of the T cell repertoire.…”
Section: Metastatic Melanomamentioning
confidence: 89%
“…One of the recent breakthroughs in cancer immunotherapy was the clinical use of anti-CTLA-4 antibodies (ipilimumab and tremelimumab), which were shown to induce tumor regression and improve the survival of patients with metastatic melanoma. [799][800][801][802][803][804][805][806][807] Although targeting CTLA-4 was initially designed to reactivate Teff cells, CTLA-4 is also highly expressed on Treg cells, with anti-CTLA-4 antibodies inducing the depletion of Treg cells in the TME through the activation of ADCC. 806,807 In addition, anti-CTLA-4 antibodies have been reported to exhibit complimentary activity with therapies targeting anti-PD-1 (nivolumab), another checkpoint inhibitor expressed on Treg cells, with their combined use being more beneficial than the use of either antibody alone.…”
Section: Adjusting the Inflammation In Innate Immunitymentioning
confidence: 99%
“… 167 , 169 , 170 The success of this regimen might have a particular positive impact on melanoma patients refractory to PD-1 blockers. 171 173 The PD-1 blocker nivolumab 174 is also being tested in combination with the STING agonist SB11285 in subjects with advanced solid tumors (NCT04096638). Only one clinical trial, enrolling patients with advanced solid tumors (NCT03956680), evaluated the safety and preliminary efficacy of ipilimumab and nivolumab together, 175 178 co-administered with the STING agonist BMS-986301.…”
Section: Sting Agonists As Cancer Therapeuticsmentioning
confidence: 99%